Conditional deletion of Rcan1 predisposes to hypertension-mediated intramural hematoma and subsequent aneurysm and aortic rupture - Silvia Villahoz (Nature Portfolio, 2018)
Constitutive deletion of Rcan1 has been previously shown to prevent Angiotensin II-induced aneurysm in mice. Here the authors show that tissue-specific inducible deletion of Rcan1 in vascular cell types predisposes to hypertension-mediated aortic rupture, intramural hematoma, and aneurysm, due to increased GSK-3b-mediated activation of ROCK and induction of a hypercontractile phenotype.